Why decentralization works and does not works? A systematic literature review - Sujarwoto, Sujarwoto (FIA UB, 2017)
This systematic literature review is purposed to elaborate why decentralization works and does not works? The results show that decentralization will increase public services at sub national level or local government when certain conditions exist. Empirical findings across developing countries in last decades show that decentralization will benefit for improving local public services when competitive and fair local election, transparency, checks and balance, citizen participation and community social capital exists. Capacity of public servants and availability of basic infrastructures is also key conditions for effective decentralization across developing countries.